2020
DOI: 10.1186/s40814-020-00591-4
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture or auricular electro-acupuncture as adjuncts to lifestyle interventions for weight management in PCOS: protocol for a randomised controlled feasibility study

Abstract: Background: Polycystic ovary syndrome (PCOS) is a prevalent women's health condition with reproductive, metabolic, and psychological manifestations. Weight loss can improve these symptoms and is a key goal; however, many women find this difficult to achieve. Acupuncture is a Chinese medical treatment that involves insertion of very fine metal needles into specific areas of the body and has been shown to be efficacious for weight loss in non-PCOS populations. However, few studies have been conducted in women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…In addition, other studies have shown that acupuncture can reduce the incidence of PCOS by changing the distribution of specific intestinal flora, increasing the content of beneficial bacteria, and maintaining the balance between the internal and external environment of the patients [ 13 ]. Ee designed a protocol to verify their hypothesis that the mechanism of acupuncture for obese PCOS patients is improving IR [ 14 ].…”
Section: Acupuncturementioning
confidence: 99%
“…In addition, other studies have shown that acupuncture can reduce the incidence of PCOS by changing the distribution of specific intestinal flora, increasing the content of beneficial bacteria, and maintaining the balance between the internal and external environment of the patients [ 13 ]. Ee designed a protocol to verify their hypothesis that the mechanism of acupuncture for obese PCOS patients is improving IR [ 14 ].…”
Section: Acupuncturementioning
confidence: 99%
“…Among the different therapeutic approaches of TCM, acupuncture is the most known in occident, where it has had marked progress in the second half of the twentieth century [45]. Acupuncture treatment involves insertion of very thin metal needles into specific areas or acupoints of the body, which are important in regulation and restoration of vegetative function [46]. Different studies demonstrate several characteristics associated with these acupoints: correspondence to a dermatome pattern [45], various types of terminal nerves [47], reduced skin electric impedance, and the presence of neurovascular bundles [48].…”
Section: Introductionmentioning
confidence: 99%